Effects of prenatal exposure to air pollution on preeclampsia in Shenzhen, China. (June 2018) - Wang, Qiong; Zhang, Huanhuan; Liang, Qianhong; Knibbs, Luke D.; Ren, Meng; Li, Changchang; Bao, Junzhe; Wang, Suhan; He, Yiling; Zhu, Lei; Wang, Xuemei; Zhao, Qingguo; et al.
Abstract: The impact of ambient air pollution on pregnant women is a concern in China. However, little is known about the association between air pollution and preeclampsia and the potential modifying effects of meteorological conditions have not been assessed. This study aimed to assess the effects of prenatal exposure to air pollution on preeclampsia, and to explore whether temperature and humidity modify the effects. We performed a retrospective cohort study based on 1.21 million singleton births from the birth registration system in Shenzhen, China, between 2005 and 2012. Daily average measurements of particulate matter <10 μm (PM10 ), sulfur dioxide (SO2 ), nitrogen dioxide (NO2 ), air temperature (T), and dew point (Td ) were collected. Logistic regression models were performed to estimate associations between air pollution and preeclampsia during the first and second trimesters, and during the entire pregnancy. In each time window, we observed a positive gradient of increasing preeclampsia risk with increasing quartiles of PM10 and SO2 exposure. When stratified by T and Td in three categories (<5th, 5th −95th, and >95th percentile), we found a significant interaction between PM10 and Td on preeclampsia; the adverse effects of PM10 increased with Td . During the entire pregnancy, there was a null association between PM10 and preeclampsia under Td  < 5th percentile. Preeclampsia risk increased by 23% (95% CI: 19–26%) when 5th < Td  < 95th percentile, and by 34% (16–55%) when Td  > 95th percentile. We also found that air pollution effects on preeclampsia in autumn/winter seasons were stronger than those in the spring/summer. This is the first study to address modifying effects of meteorological factors on the association between air pollution and preeclampsia. Findings indicate that prenatal exposure to PM10 and SO2 increase preeclampsia risk in Shenzhen, China, and the effects could be modified by humidity. Pregnant women should limit air pollution exposure, particularly during humid periods. Graphical abstract: Image 1 Highlights: Prenatal exposure to PM10 and SO2 increases preeclampsia risk. The 1st, 2nd trimester and entire pregnancy are significant exposure time windows. Effects of PM10 exposure on preeclampsia are modified by air humidity. Abstract : Main finding : Prenatal exposure to PM10 and SO2 increased preeclampsia risk, and the effect of PM10 was modified by humidity.